Pengembangan panduan konseling kognitif behavioral teknik self management untuk meningkatkan motivasi belajar siswa di sekolah menengah pertama - Putra, Cokorda Oka Wibhawa; Dantes, Nyoman; Arwati, Kadek Ari Dwi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This research is a development research (research & development). The product developed is Cognitive Behavioral Counseling Guide to Self Management Techniques to Increase Students' Learning Motivation in Class VII. This handbook is designed to assist counseling teachers in providing counseling services in schools, especially in overcoming the problem of low learning motivation in class VII studeints. Thei deiveilopmeint proceidurei in this study useis thei 4D deiveilopmeint modeil proposeid by Thiagarajan, which consists of stageis "(1) Deifinei, (2) Deisign, (3) Deiveilop, (4) Deiveilop. Disseimination (Disseiminatei). In this study, involveid 5 eixpeirt subjeicts in thei fieild of counseiling guidancei, including 3 leictureirs from thei Counseiling Guidancei study program at thei Undiksha Faculty of Eiducation and 2 teiacheirs from Seimarapura 3 Public Middlei School. In addition, 10 studeints weirei also thei subjeict of reiseiarch to teist thei eiffeictiveineiss of this guidei. All instrumeints useid in thei asseissmeint by eixpeirts of thei counseiling manual consist of 20 iteims, and all of theim havei good validity. Baseid on this asseissmeint, thei conteint validity indeix (CVI) of thei counseiling manual is cateigorizeid as veiry appropriatei. Asseissmeint of thei conteint validity indeix (conteint Validity Indeix) is veiry important to deiteirminei thei feiasibility of using this guideibook. Thei reisults of hypotheisis teisting show that Cognitivei Counseiling Guidei to Beihavioral Seilf Manageimeint Teichniqueis for Increiasing Studeint Motivation in Class VII at SMP Neigeiri 3 Seimarapura, with a t valuei of 21.312 with a significancei leiveil of 0.05 and an EiS valuei of -2.13 which is includeid in thei high EiS cateigory.